Demand Analysis and Why the Poor May Pay More - Reinhardt, P. G. (Quarterly Journal of Economics, 1976)
I. Classical demand analysis and cross-sectional price elasticities, 509.—II. Price discrimination and the new theory of demand, 510.—III. Conclusion, 512.